PEMBERDAYAAN MAHASISWA MELALUI LITERASI BACA BERBASIS PERPUSTAKAAN ONLINE - nurul afifah; Trisilia Devana; Nopa Yusnilita; Inawati; Lasmiatun; Ratu Aysa (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2026)
The objective of this Community Service Program is to improve students' reading literacy and digital literacy skills through practical training in the use of online libraries. The program is implemented by delivering material on the importance of reading and digital literacy, practical training in the use of online libraries, including registration, searching, and downloading materials, and students independently practicing the material taught with team support. The method used in this program is a participatory-educational approach. The implementation team not only passively delivers material but also encourages active student interaction and participation through: Interactive Workshop: Using presentations, discussions, and Q&A methods, Hands-on Practice: Providing students with the opportunity to directly experience using the online library using the provided facilities, Intensive Mentoring: Providing personal assistance to any participant experiencing technical difficulties. Based on data analysis from the post-activity questionnaire, the following results were obtained: 95% of participants stated that their understanding of online libraries had significantly improved, 85% of participants felt more confident in searching for digital reference sources, 75% of participants promised to use the online library more often for academic purposes. Qualitative observations during the training showed that all participants were able to follow each stage of the training effectively. They no longer hesitated to ask questions and engage in discussions, indicating that the approach used was effective in building participant confidence.